Diagnosis, management and treatment of the Alport syndrome - 2024 guideline on behalf of ERKNet, ERA and ESPN - Torra, Roser; Lipska-Zietkiewicz, Beata; Acke, Frederic; Antignac, Corinne; Becker, Jan Ulrich; Cornec-Le Gall, Emilie; Van Eerde, Albertien M; Feltgen, Nicolas; Ferrari, Rossella; Gale, Daniel P; Gear, Susie; Gross, Oliver; et al. (Nephrology, dialysis, transplantation. NDT plus, 2025)
Glomerular nephropathy resulting from the genetic defects in COL4A3/4/5 genes including the classical Alport syndrome is the second most common hereditary kidney disease characterized by persistent haematuria progressing to the need for kidney replacement therapy, frequently associated with sensorineural deafness, and occasionally with ocular anomalies.Diagnosis and management of COL4A3/4/5 glomerulopathy is a great challenge due to its phenotypic heterogeneity, multiple modes of inheritance, variable expressivity, and disease penetrance of individual variants as well as imperfect prognostic and progression factors and scarce and limited clinical trials, especially in children.As a joint initiative of the European Rare Kidney disease reference Network (ERKNet), European Renal Association (ERA Genes&Kidney), and European Society for Paediatric Nephrology (ESPN) Inherited renal disorders working group, a team of experts including adult and paediatric nephrologists, kidney geneticists, audiologists, ophthalmologists, and a kidney pathologist wereselected to perform a systematic literature review on 21 clinically relevant PICO (Patient or Population covered, Intervention, Comparator, Outcome) questions. The experts formulated recommendations and formally graded them at a consensus meeting with input from patient representatives and a voting panel of nephrologists representing all regions of the world.Genetic diagnostics comprising joint analysis of COL4A3/4/5 genes is already the key diagnostic test during the initial evaluation of an individual presenting with persistent haematuria, proteinuria, kidney failure of unknown origin, focal segmental sclerosis of unknown origin, and possibly cystic kidney disease. Early renin-angiotensin system blockade is the standard of care therapy; sodium-glucose cotransporter-2 inhibitors may be added in adults with proteinuria and chronic kidney disease. Relatives with heterozygous COL4A3/4/5 variants should only be considered as the last possible resource for living kidney donation.This guideline provides guidance for the diagnosis and management of individuals with pathogenic variants in COL4A3/4/5 genes.